Rights of women during marriage from Qura’nic perspectives with cross-reference to the law in Malaysia: an analysis - Ahmad, Nadzrah; Ghazali, Norzulaili; Othman, Roslina; Ismail, Nurul Syuhada; Mohd Yusoff, Rahmawati (Serials Publication LTD, 2019)
Women’s rights issues in relation to marriage are the most significant topic of debate in many countries. Marriage is regularly portrayed as an “oppressive sphere” for women, with their rights being oppressed the moment they enter a marriage contract, especially in Islam. However, in many cases, Islamic matrimony has been demonstrated to liberate women, preserve their honour and place in society, and abolish injustice when guided by principles from the Qur’an an d t he Sun nah of Prophet Muhammad (s.a.w.). In gen eral, misconception regarding the Muslims is caused by cultural interpretation and malpractice of the original Islamic teachings, which have tainted the true Islamic ideal. This study addresses the rights of women in marriage from the Qur’anic perspective and from the maqasid shariah approach. It also examines the concept by referring to the laws in Malaysia and explores the issue of whether the Malaysian laws uphold the rights of women or not. The discussion is based on the related Qur’anic verses including their tafsir, and supported with the Hadith of the Prophet. Consecutively, the paper analyses the rights of women in the laws of Malaysia, with support from any related cases law. This library research examines the topic from the viewpoints of the Qur’an and the Sunnah as the primary sources of Islamic law, followed by an analysis on the statutes of laws in Malaysia and several relevant decided cases. In addition, the opinions of scholars regarding the issue on the rights of women in marriage are also taken into consideration in the analysis. It is hoped that the study may provide a clear reference and guideline regarding the rights of women in marriage from both the Islamic and Malaysian laws as this topic is highly significant and beneficial to numerous parties in the present day.